Government Budget Efficiency on Economic Growth - Indah Lia Puspita; Agus Juvindi; Liayana Safitri; Maya Lestari (Arden Jaya Publisher, 2026)
This study aims to analyze the impact of budget efficiency on economic growth, both nationally and regionally in Indonesia. Budget efficiency is not merely about saving government spending, but rather emphasizes the optimization of resources so that every rupiah spent provides maximum benefits for society and economic development. The results of the study indicate that government budget efficiency has significant positive and negative impacts on economic growth. The positive impacts of budget efficiency carried out by the government are as an increase in a country's competitiveness, then as inflation control, as well as in several sectors that greatly influence economic growth such as infrastructure, industry, agriculture and MSMEs. The negative impacts caused by government budget efficiency can result in slowing economic growth due to budget cuts in vital sectors, then a decrease in people's purchasing power, a reduction in the workforce resulting in soaring unemployment rates. In addition, budget efficiency carried out by the government without strategic planning can also lead to development inequality between regions, especially in underdeveloped areas that are highly dependent on government funding allocations. Therefore, the implementation of budget efficiency must be accompanied by appropriate policies to continue to encourage inclusive and sustainable economic growth, and ensure the equitable distribution of the benefits of budget efficiency to all levels of society.